Hero stone depicting the hero wearing a distinctive headgear riding on a horse - Temples of India Project Team (Jio Institute, 2024)
Seen here is an example of a hero stone without an inscription, showcasing a slightly different style. The niche inside which the hero is depicted is a low relief niche with an arch design. The drapery of the hero and the celestial damsel accompanying him is uniquely rendered. The hero is depicted wearing a distinctive headgear resembling those worn in the Rajasthan region. In the corner of the niche, there is a sun motif, possibly symbolizing that the hero’s valour will endure eternally.